Wilson disease - Członkowska, Anna; Schilsky, Michael L. (Handbook of clinical neurology, 2017)
"Wilson Disease provides a comprehensive guide on this inherited genetic disorder that has devastating consequences for both the liver and neurologic/psychiatric health. This disease is of increasing interest to neurologists, hepatologists, and geneticists, but when the disease is diagnosed early, it is treatable, with patients living normal lives. This volume describes the molecular pathophysiology of WD and the clinical and pathological effects of copper. Separate sections address both diagnosis and medical and surgical approaches to treatment. Both adult and pediatric perspectives on diagnosis and treatment are addressed, and a section on genetics highlights advances in molecular diagnostics. Patient support groups that can aid in coping with this disease are also discussed, as are animal models for those interested in basic research on cell biology, pathophysiology, and treatment"--Publisher's description.